Penyusunan Modul Pembelajaran Sebagai Upaya Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Friseza Nayla Aribah Zahra; Lufinda Amalia; Tamara Noviani Fujia Suchi; Sofyan Iskandar (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Learning planning is necessary to create learning that runs optimally. One form of planning is a learning module, which plays an important role in helping teachers develop structured learning in accordance with the Merdeka Curriculum. This study aims to determine the importance of preparing teaching modules as an effort to optimize the teaching and learning process at school. The research method used is library research with a qualitative approach, where data is obtained from various literature sources such as relevant books and journals. The results of the study show that a good learning module can improve concept understanding, active student involvement, and the effectiveness of the teaching-learning process. Modules that are prepared according to procedures and complete components provide clear direction for teachers and support the achievement of student learning outcomes. In conclusion, the preparation of systematic and innovative teaching modules is an effort to optimize the quality of education, especially at the primary school level.